PHYSICAL QUALITY AND NUTRIENT CONTENT OF DUCKWEED FERMENTED BY Saccharomyces cerevisiae - I N. A. M., Diarta; Suryani, N. N.; Suarna, I W. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the physical quality and nutrient content of fermented duckweed using Saccharomyces cerevisiae. The research material was duckweed which was obtained by taking it in nature, duckweed was fermented using Saccharomyces cerevisiae starter which was fermented for 72 hours (3 days). The design used is descriptive comparative by comparing unfermented duckweed (DNF) and fermented duckweed (DF). The variables observed in physical properties were density, water absorption, water solubility, and nutrient content, namely dry matter, organic matter, ash, crude protein, crude fiber. The results showed that the densities of DNF and DF were 321.58 g/ml and 456.10 g/ml, respectively, water absorption capacities of 3.89% and 3.49%, water solubility of 8.71% and 13.69%, dry matter 90.74% and 92.90%, organic matter 68.41% and 74.29%, ash 31.58% and 25.70%, crude protein 22.17% and 23.87%, crude fiber 17 .60% and 16.24%. Based on the results of this study, it can be concluded that fermented duckweed can increase density, water solubility, dry matter, organic matter, and crude protein, but there is a decrease in the absorption of water, ash and crude fiber.